Ai margini di Aristofane: una lettura umanistico-rinascimentale di Pluto e Nuvole (ACME, 2021)
Humanist exegesis to Aristophanes’ plays has not yet been illuminated in the Aristophanic studies. Fragments of humanistic readings of the Aristophanic corpus still lie unedited and unexplored in some of the recent manuscripts of Greek Comedy. In this essay, I shall examine a number of marginal and interlinear glosses, almost unknown until now, left in a fifteenth-century manuscript - Vat. Ottob. gr. 210 - by a humanist Latin reader of Aristophanes’ Plutus and Nubes. This hitherto neglected codex is especially interesting because of its significance for the reception and interpretation of Ancient Comedy during the Renaissance age.